A proteção do (ao) trabalho : uma reflexão sobre a suficiência da reforma laboral em face à nova realidade de trabalho no Brasil e na Espanha - Marques, Vinícius Lima (2021)
Labor legislation was designed to protect the classically subordinate worker from the forces of capital, through an employment relationship. Over time and, especially, with the advent of globalization and the emergence of new technologies, the way in which labor is exercised and how capital is structured has substantially changed, changing the paradigms of the labor relationship and leading to the crisis of the labor market, concept of legal subordination, an essential requirement for the recognition of a relationship as being employment and, therefore, subject to the protective framework of labor legislation. Reformist movements in labor legislation are emerging in several countries, notably in Brazil and Spain, the main focus of the present study. Therefore, the aim is to assess whether Labor Law is sufficiently prepared for the new modalities of the work relationship, considering also the labor reforms carried out in Brazil and Spain. Today still exists of classic employment relationships, most of the work relationships no longer serve as a paradigm for classic legislation in the form in which it was conceived, culminating in the need to update legislation to implement protection, especially work provided through digital platforms. Thus, instead of discussing the expansion of traditional concepts, it is prudent to discuss the institution of distinct legal figures with specific protections, primarily centered on the principle of fraternity, with division of responsibility among social actors, in order to complement the freedom and equality. It is also noticed that the legislative progress with the reform of the labor legislation should not be considered as a social setback, as it promotes protection of the excluded, not affected by the protection of the classic Labor Law. In any case, in view of technological progress that will further modify labor activity and potentially take the place of workers, there is a need to improve the skills of workers, especially to enable them to adapt in the face of constant changes. The present study is linked to the Pontifical Catholic University do Rio Grande do Sul, in Brazil, in the Postgraduate Program in Law, area of concentration Constitutional Fundamentals of Public Law and Private Law, in the line Efficiency and of the Effectiveness Constitution and Fundamental Rights in Public Law and Private Law, with a focus on the Efficacy and Effectiveness of the Constitution and Fundamental Rights in Labor Law, line of research by Advisor Professor Doctor Gilberto Stürmer, and with the University of Valencia, in Spain, due to the orientation of the Professor Doctor Fernando Fita Ortega, linked to the research line Labor Law and Social Security.